A three‐dimensional computational fluid dynamics model of shear stress distribution during neotissue growth in a perfusion bioreactor. Issue 12 (14th July 2015) - Guyot, Y.; Luyten, F.P.; Schrooten, J.; Papantoniou, I.; Geris, L.
ABSTRACT: Bone tissue engineering strategies use flow through perfusion bioreactors to apply mechanical stimuli to cells seeded on porous scaffolds. Cells grow on the scaffold surface but also by bridging the scaffold pores leading a fully filled scaffold following the scaffold's geometric characteristics. Current computational fluid dynamic approaches for tissue engineering bioreactor systems have been mostly carried out for empty scaffolds. The effect of 3D cell growth and extracellular matrix formation (termed in this study as neotissue growth), on its surrounding fluid flow field is a challenge yet to be tackled. In this work a combined approach was followed linking curvature driven cell growth to fluid dynamics modeling. The level‐set method (LSM) was employed to capture neotissue growth driven by curvature, while the Stokes and Darcy equations, combined in the Brinkman equation, provided information regarding the distribution of the shear stress profile at the neotissue/medium interface and within the neotissue itself during growth. The neotissue was assumed to be micro‐porous allowing flow through its structure while at the same time allowing the simulation of complete scaffold filling without numerical convergence issues. The results show a significant difference in the amplitude of shear stress for cells located within the micro‐porous neo‐tissue or at the neotissue/medium interface, demonstrating the importance of taking along the neotissue in the calculation of the mechanical stimulation of cells during culture.The presented computational framework is used on different scaffold pore geometries demonstrating its potential to be used a design as tool for scaffold architecture taking into account the growing neotissue. Biotechnol. Bioeng. 2015;112: 2591–2600. © 2015 Wiley Periodicals, Inc. Abstract : Current computational fluid dynamic approaches for tissue engineering bioreactor systems have been mostly carried out for empty scaffolds. The effect of 3D cell growth and extracellular matrix formation (porous neotissue growth), on its surrounding fluid flow field is a challenge yet to be tackled. In this work, curvature‐driven neotissue growth was employed in order to map shear stress distribution at the interface but also within the porous domain representing the neotissue.